2016
DOI: 10.1111/mmi.13462
|View full text |Cite
|
Sign up to set email alerts
|

The Aspergillus fumigatus conidial melanin production is regulated by the bifunctional bHLH DevR and MADS‐box RlmA transcription factors

Abstract: Melanins play a crucial role in defending organisms against external stressors. In several pathogenic fungi, including the human pathogen Aspergillus fumigatus, melanin production was shown to contribute to virulence. A. fumigatus produces two different types of melanins, i.e., pyomelanin and dihydroxynaphthalene (DHN)-melanin. DHN-melanin forms the gray-green pigment characteristic for conidia, playing an important role in immune evasion of conidia and thus for fungal virulence. The DHN-melanin biosynthesis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 48 publications
0
39
0
1
Order By: Relevance
“…In Aspergillus nidulans , Bh1 is involved in the regulation of penicillin biosynthesis and DevR is required for both asexual and sexual development (Caruso et al ., ; Tuncher et al ., ). In Aspergillus fumigatus , DevR regulated dihydroxynaphthalene (DHN)‐melanin synthesis (Valiante et al ., ), and SrbA is critial for cell polarity, hypoxia adaptation, and virulence (Willger et al ., ; Dhingra et al ., ). In Aspergillus oryzae , SclR promotes sclerotial formation and EcdR is involved in the early stages of conidiophore development (Jin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In Aspergillus nidulans , Bh1 is involved in the regulation of penicillin biosynthesis and DevR is required for both asexual and sexual development (Caruso et al ., ; Tuncher et al ., ). In Aspergillus fumigatus , DevR regulated dihydroxynaphthalene (DHN)‐melanin synthesis (Valiante et al ., ), and SrbA is critial for cell polarity, hypoxia adaptation, and virulence (Willger et al ., ; Dhingra et al ., ). In Aspergillus oryzae , SclR promotes sclerotial formation and EcdR is involved in the early stages of conidiophore development (Jin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the deletion caused wrinkled colonies and resulted in a yellow pigment, and the strain did not form conidia on minimal agar plates. Additionally, DevR also regulates conidial melanin production in Aspergillus fumigatus (19). As an essential component of the cell wall, melanin plays a significant role in protecting organisms from external stresses (20).…”
mentioning
confidence: 99%
“…Among these genes, pksP, a polyketide synthase gene, plays a core role. It has been reported that DevR and another MADS box transcription factor, RlmA, may bind to the pksP promoter to induce the transcription activity of pksP, thus regulating melanin production (19).…”
mentioning
confidence: 99%
See 2 more Smart Citations